Losing control, learning to fail: leveraging techniques from improvisational theatre for trust and collaboration in transdisciplinary research and education - Marius Korsnes; Sophia Efstathiou; Sven Veine; Martin Loeng; Marianthi Papalexandri Alexandri; Giovanni De Grandis; Giulia Sonetti (Global Social Challenges Journal)
This article explores the transformative potential of improvisational techniques in reshaping interdisciplinary and transdisciplinary (ITD) learning environments offering art-based exercises and tools for this work. By integrating active research with improvisational methods from theatre and music, we propose a pedagogical shift that transcends traditional academic roles and disciplinary boundaries, fostering a culture of co-creation, mutual learning and innovation. This approach aims to tackle the inherent challenges of ITD research and thus enhance ITD research groups’ ability to address complex societal ‘Grand Challenges’. We argue that improvisation within both ITD research and educational communities serves as a crucial catalyst for nurturing trust, embracing failure as a growth opportunity, and redefining success. Embodied practices based on improvisation help bridge the gap between theoretical knowledge and practical applications, enabling academics to navigate the complexities of collaboration and engage in shared learning experiences. This article introduces techniques from improvisational theatre aimed at fostering trust and collaboration in transdisciplinary research and educational settings. Drawing on over 25 years of combined research experience, we show how these tools enhance mutual understanding and collective problem-solving among students and research teams. Ultimately, we advocate integrating conventional knowledge delivery models with a framework characterised by regenerative practices, care and explorative processes. This integrated approach would offer new opportunities for addressing the intertwined wicked problems our world faces today, promoting a more inclusive, participatory and creatively fulfilling academic community.